2008
DOI: 10.1159/000157177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Cholecalciferol Supplementation on Mineral Metabolism and Calciotropic Hormones in Chronic Kidney Disease

Abstract: Background: Data on the efficacy and safety of long-term vitamin D supplementation in chronic kidney disease (CKD) are scarce. We assessed the effects of the 12-month vitamin D3 treatment on mineral metabolism and calciotropic hormones in patients with CKD stages 2–4. Methods: Eighty-seven patients (mean age 66 years, men/women 33/54) were randomized to cholecalciferol treatment with either 5,000 or 20,000 IU/week. Serum calcium, phosphate, 25(OH)D3, 1,25(OH)2D3, PTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…Many studies have evaluated vitamin D (either cholecalciferol or ergocalciferol) as a treatment for vitamin D insufficiency or SHPT in adults with predialysis CKD [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42]. Most were open-label studies and some were conducted in patients exhibiting SHPT.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated vitamin D (either cholecalciferol or ergocalciferol) as a treatment for vitamin D insufficiency or SHPT in adults with predialysis CKD [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42]. Most were open-label studies and some were conducted in patients exhibiting SHPT.…”
Section: Discussionmentioning
confidence: 99%
“…Okša et al 36 reported similar decreases in PTH using either 5,000 IU or 20,000 IU cholecalciferol per week (~714 or 2857 IU/day). Hari et al 37 reported greater median reductions in PTH in Stage 2 (38.5%) compared with Stages 3 (25.2%) and 4 (15.2%).…”
Section: Resultsmentioning
confidence: 90%
“…Of the 17 studies, two studies were double-blind, randomized placebo-controlled trials; 29 , 30 6 were randomized controlled trials comparing cholecalciferol/ergocalciferol to active vitamin D analogs, 31 , 32 no treatment, 33 - 35 or different dose of cholecalciferol; 36 4 were prospective, observation trials of cholecalciferol 37 or ergocalciferol 38 - 40 and 4 were retrospective, observational studies of ergocalciferol 41 - 44 . One study 45 appears to be a secondary analysis of a parent study, 36 thus duplicate analyses are only reported for the parent study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations